Membangun Keluarga Cerdas Finansial Melalui Edukasi Literasi Keuangan Ibu PKK Di Desa Asrikaton – Kabupaten Malang - Marlina Magdalena; Annisa Fatimah; Yusna; Santi Widiyanti (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2026)
Purpose – This community service program aimed to improve household financial literacy among housewives and children in Urek-Urek Hamlet, Asrikaton Village, Pakis District, Malang Regency, through a community-based participatory strategies. Design/methodology/approach – The program adopted a community-based participatory approach involving PKK partners in all stages, from needs assessment to evaluation. Interactive training was delivered using contextual games (Belanja Bijak, Cerdas Cermat Hemat, and Tangkap Risiko), scenario-based discussions, and visual media, complemented by a session on safe gold investment as a simple long-term saving strategy. Findings – The approach generated high enthusiasm and active participation, with post-test results indicating a 41% improvement in financial literacy scores. Participants reported behavioral changes, including budgeting, expense recording, avoiding unplanned online loans, and initiating periodic gold saving. The formation of the “Ibu Cerdas Finansial” learning community and the integration of financial literacy into monthly PKK meetings demonstrated strong sustainability potential.Originality/value – This program uniquely combines participatory education, gamification, and culturally relevant financial practices through PKK networks, offering a replicable and scalable model for strengthening household financial resilience in rural communities.